Analysis of patent protection activities in Vietnamese higher education institutions: Trends and challenges - Nguyen , Phúc Quân (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Patents play an important role in the intellectual property system by protecting inventions and promoting innovation. This study analyzes patent protection activities at higher education institutions in Vietnam from 1980 to 2024, focusing on application numbers, grant rates, processing times, and procedural characteristics. Over the 44-year period, 1,894 applications were submitted, with 594 patents granted, resulting in a success rate of approximately 30%. The average processing time was 1,145 ± 561 days (about 3.1 years), with a median of 1,013 days (2.8 years). The 2021–2024 period showed improvement, with average processing time reduced to 1,055 ± 427 days. However, compared to international institutions, Vietnam still has a lower grant rate and longer processing time. The findings indicate that, despite procedural progress, patent protection activities in Vietnamese universities remain limited, reflecting disparities in research capacity. To enhance effectiveness, it is necessary to reform the patent granting process, shorten processing times, and implement financial support policies to promote innovation. These measures will help strengthen research capabilities and contribute to the sustainable development of the higher education system.